The Specifics of Functioning of the Personal Proper Name (Proceedings of Southern Federal University. Philology, 2020)
The article researches the specifics of how personal proper names function in the Russian and the Chinese paroemia genres. Proverbs and sayings are traditionally considered paroemia because they represent a collective evaluation of various situations of life. The idioms that express a position of evaluation towards the current events are not included in the category of paroemiological units, for their components have lost their lexical meaning and acquired a high degree of reinterpretation.The article uncovers the types and the forms of the personal name that perform different functions in the Russian and the Chinese paroemia genres. Anthroponyms, mythonyms, chrononyms and hagionyms can be considered characteristic for the Russian proverbs and sayings, and the subjectiveevaluative forms are predominant in the Russian proverbs, where the name functions in a generalized, collective meaning. While the Russian paroemia genres express evaluative connotation explicitly, the Chinese proverbs and sayings are based on the association of a specific personal name, which is known to the majority of the native speakers, with a real historical figure, a specific mythological character or a personality of fiction.Key words: evaluative connotation, personal proper name, proverbs, sayings, yanyu.DOI 10.18522/1995-0640-2020-3-30-37